Time and Effort Required for Tissue Acquisition and Submission in Lung Cancer Clinical Trials - Garcia, Sandra (Clin Lung Cancer, 2017)
BACKGROUND: Increasingly, analysis of tumor tissue samples for predictive and pharmacodynamic biomarkers is incorporated into lung cancer clinical trials. We determined the time and effort required for tissue acquisition and submission. METHODS: We analyzed data from patients enrolled 2009–2016 at UT Southwestern on lung cancer trials with mandatory or optional submission of tumor tissue. We collected dates of treatment-related events and staff communications; nature of tissue requirement and biomarker analysis; and location of archival tissue. Associations between case characteristics, clinical intervals, and number of staff communications were analyzed by Fisher’s exact test, Wilcoxon two-sample test, and Kruskal-Wallis test. RESULTS: We identified 129 patients enrolled in 19 clinical trials, of whom 108 (84%) ultimately received study therapy. For cases in which tissue submission was required if available or optional, 16% and 0%, respectively, had tissue sent. The median interval between consent and treatment was 28 (IQR 11–43) days if tissue was requested and 7 (IQR 6–13) days if tissue was not requested (P<0.001). Among cases with requested tissue, the median number of related research staff communications was 3 (range 0–10). Over time, the number of staff communications increased (P<0.001). Location of archival tissue was not associated with number of staff communications or treatment intervals. CONCLUSION: Lung cancer clinical trial requirements for tissue acquisition and submission impact time to treatment initiation and require increasing staff effort. Improved systems to expedite these processes, as well as use of blood- or imaging-based biomarkers, may help address these issues.